How do you evaluate e^( (3 pi)/2 i) - e^( ( pi)/3 i)e3π2ieπ3i using trigonometric functions?

1 Answer
Feb 26, 2017

Use Euler's identity:

e^(ix) = cosx + isinxeix=cosx+isinx

Thus:

e^((3pi)/2i) - e^(pi/3i)e3π2ieπ3i

= cos((3pi)/2) + isin((3pi)/2) - (cos(pi/3) + isin(pi/3))=cos(3π2)+isin(3π2)(cos(π3)+isin(π3))

= cancel(cos((3pi)/2))^(0) + isin((3pi)/2) - cos(pi/3) - isin(pi/3)

= -i - 1/2 - sqrt3/2i

= color(blue)(-1/2 + (-1 - sqrt3/2)i)

So, for the form a + bi, a = -1/2 and b = -1 - sqrt3/2.